Sustainability practices in container terminals in Brazil - Tomaz Alexandre Calcerano; Wilson de Castro Hilsdorf (Production)
Abstract Paper aims This paper aims to investigate which sustainability practices are being applied in port terminals in Brazil and to identify the driving forces and obstacles to the implementation of these practices. Originality The research contributes to fill gaps that still remain in the literature, such as the need to identify and analyze sustainability requirements in the port industry in a more tangible way, bringing new evidence to a better understanding of how the port industry perceives and addresses sustainability issues. Research method The paper presents an in-depth multiple case study in the five largest terminals in Brazil, which correspond to approximately 60% of the Brazilian handling of containers. Main findings The results present evidence of the evolution of the commitment to environmental preservation and the progressive dissemination of sustainability practices. The main difficulties are the high costs and lack of support from the port authority to encourage the implementation of some practices. Implications for theory and practice This study aimed to disclose sustainability practices adopted at container terminals in Brazil, as well as provide some content, both for academia and companies, that may assist in developing new research on this theme and implementing these practices in other organizations.